2017
DOI: 10.1186/s40842-017-0051-2
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on the impact of painful diabetic peripheral neuropathy in a multicultural population

Abstract: BackgroundSince few studies have characterized painful diabetic peripheral neuropathy (pDPN) symptoms in multicultural populations, this study fielded a survey to better understand pDPN and its impact in African-American, Caucasian, and Hispanic populations.MethodsKelton fielded a survey by phone or Internet, in English or Spanish, among adults with pDPN symptoms in the United States between August and October 2015; African-Americans and Hispanics were oversampled to achieve at least 500 subjects for each grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 15 publications
0
21
0
3
Order By: Relevance
“…Other studies have also reported that a large proportion of patients with PDPN were not diagnosed, 61.5% in Germany 7 and 12.5% in the UK 8 . Major hurdles limiting the diagnosis of PDPN are that patients with painful symptoms do not attribute them to diabetes and fail to report them to their physician 8,9 , and of course screening is not currently advocated for PDPN, only for those at high risk of foot ulceration 31 . Given that we have identified age, duration of diabetes and the presence of impaired vibration perception as major determinants for PDPN 1,5,6,10 , one could advocate screening for PDPN in at least diabetes patients who are older, have a longer duration of diabetes and impaired vibration perception.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have also reported that a large proportion of patients with PDPN were not diagnosed, 61.5% in Germany 7 and 12.5% in the UK 8 . Major hurdles limiting the diagnosis of PDPN are that patients with painful symptoms do not attribute them to diabetes and fail to report them to their physician 8,9 , and of course screening is not currently advocated for PDPN, only for those at high risk of foot ulceration 31 . Given that we have identified age, duration of diabetes and the presence of impaired vibration perception as major determinants for PDPN 1,5,6,10 , one could advocate screening for PDPN in at least diabetes patients who are older, have a longer duration of diabetes and impaired vibration perception.…”
Section: Discussionmentioning
confidence: 99%
“…Despite having a serious impact on the patient's quality of life, PDPN is underdiagnosed and undertreated 7,8 . Patients with painful symptoms are often unaware that the pain is related to diabetes, and do not report it to their clinician 8,9 . Screening patients at high risk for PDPN should allow timely identification and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic peripheral neuropathy is present in up to half of all patients with long‐standing diabetes mellitus, and up to one‐third will develop diabetic peripheral neuropathic pain (DPNP) DPNP is a major cause of morbidity, often worsening quality of life, as well as being associated with a significant economic burden. DPNP often results in sleep disturbance, and the constant tiredness from disturbed sleep and painful symptoms during the day leads to limitations in daily activities and work productivity. DPNP symptoms are also frequently associated with depression and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…В условиях роста заболеваемости ожидается увеличе-ние распространенности ранних и поздних диабетиче-ских осложнений с поражением сердечно-сосудистой, нервной системы, органа зрения [7][8][9]. Нередко первым поводом для обращения пациента к врачам различных специальностей являются не классические проявления гипергликемии, а симптомы осложнений СД: полинейро-патия, ретинопатия, нефропатия, хроническая сердечная недостаточность, язвенные дефекты стоп и др.…”
Section: неврологияunclassified
“…Далее, по мере вовлечения в патологический процесс НЕВРОЛОГИЯ крупных миелинизированных волокон, появляются боле-вые ощущения: от покалывания, жжения до выраженного болевого синдрома [7,16]. Стойкая невропатическая боль доставляет существенные страдания пациентам, является одной из сложных проблем в лечении больных СД.…”
Section: неврологияunclassified